A Case of Acute Interstitial Nephritis After Two Doses of the BNT162b2 SARS-CoV-2 Vaccine - Mira FS (Dove Medical Press, 2021)
Filipe S Mira,1,2,* Jóni Costa Carvalho,3,* Patrícia Amaral de Almeida,4 Ana Carolina Pimenta,1 Iolanda Alen Coutinho,3 Carolina Figueiredo,1 Luís Rodrigues,1,2 Vítor Sousa,2,5 Emanuel Ferreira,1,2 Helena Pinto,1,2 Luís Escada,1,2 Ana Galvão,1,2 Rui Alves1,2 1Nephrology Department, Coimbra University Hospital, Coimbra, Portugal; 2Coimbra University Faculty of Medicine, Coimbra, Portugal; 3Allergy and Clinical Immunology Department, Coimbra University Hospital, Coimbra, Portugal; 4Internal Medicine Department, Figueira da Foz Hospital, Figueira da Foz, Portugal; 5Pathological Anatomy Department, Coimbra University Hospital, Coimbra, Portugal*These authors contributed equally to this workCorrespondence: Filipe S Mira Rua Alfredo Lopes Xisto, nº 36, Coimbra, 3000-020, PortugalTel +351 932463036Email filipemira@netcabo.ptBackground: The development of vaccines to prevent COVID-19 breakouts came with highly positive results but some unexpected side effects. Rare side effects have been seen with the BNT162b2 SARS-CoV 2 vaccine.Case Presentation: We present the case of a 45-year-old female patient who developed an acute kidney injury needing urgent hemodialysis one week after the second administration of the BNT162b2 SARS-CoV 2 vaccine. She developed a macular rash on her lower limbs and palms as well. A kidney biopsy was performed 10 days after vaccine inoculation, diagnosing acute interstitial nephritis and acute tubular necrosis with cellular casts. The patient was treated with three corticosteroid pulses followed by daily prednisolone. We witnessed clinical improvement 4 days after the initial corticosteroid treatment with progressive recovery of kidney function and hemodialysis withdrawal. After 2 weeks, the patient had recovered her kidney function. Immunophenotyping was performed, diagnosing a hypersensitivity to the vaccine and the polyethylene glycol excipient.Conclusion: Patients may develop acute reactions to vaccines. In this case, symptoms seem to correlate significantly with its inoculation and, although this case had a favourable outcome, these side effects must be made aware for clinicians and patients.Keywords: acute kidney injury, acute interstitial nephritis, proteinuria, COVID-19 vaccine